Dosing with Lactipro decreases forage intake and manure output - Miller, K.A.; Van Bibber-Krueger, C.L.; Aperce, C.C.; Alvarado, C.A.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
High-concentrate diets consisting of cereal grains and grain byproducts have high energy density compared with forage-based diets. To avoid digestive disorders, cattle must be adapted to concentrates, which often entails feeding a series of step-up diets that contain progressively less roughage over a 2- to 3-week period. This allows the microbial population to adapt to fermentation of the starches and sugars that are present in high-concentrate diets. If cattle are not properly adapted to concentrate-based diets, lactic acid, which is produced by opportunistic starch-fermenting bacteria like Streptococcus bovis, can accumulate, predisposing the animal to acidosis. Diets used during the adaptation phase are by nature less digestible than the final finishing diet, which results in increased manure output and suboptimal performance during the adaptation period. Lactipro, a relatively new probiotic drench containing the lactate-utilizing bacteria Megasphaera elsdenii, has been utilized effectively to accelerate the adaptation of cattle from roughages to concentrate-based diets. Our objective was to determine the impact on diet digestibility and manure output in cattle dosed with Lactipro (MS Biotech, Inc., Wamego, KS) and placed directly onto high-concentrate diets without prior adaptation.
Keywords: Lactipro; Forage; Manure; Performance